The Relationship Between Angiotensin-Converting Enzyme Gene I/D Polymorphism and Psoriasis, Including Psoriasis with Comorbid Hypertension and Diabetes - Liu, Jiayun; Sun, Rui; Gao, Guomin; Zhang, Mogen; Fan, Huiping; Ma, Xiaonan; Yu, Yanhong; Yuan, Yanmei; Zhang, Lulu; Niu, Changying (Clinical, cosmetic and investigational dermatology, 2024)
The relationship between angiotensin-converting enzyme (ACE) insertion/deletion (I/D) gene polymorphism and psoriasis remains unclear. This study aims to analyze the association between ACE gene I/D polymorphism and the risk of psoriasis vulgaris in the Chinese Han population and to examine the correlation between ACE gene I/D polymorphism and psoriasis with comorbid hypertension and diabetes. A total of 358 patients with psoriasis vulgaris and 347 age- and sex-matched healthy volunteers from the Chinese Han population were selected. Clinical data, including blood pressure and fasting blood glucose, were collected from the patients. The ACE gene I/D polymorphism was analyzed using polymerase chain reaction (PCR). The association between ACE gene I/D polymorphism and psoriasis vulgaris, as well as comorbid hypertension and diabetes, was analyzed using the Pearson -test. The frequency of the ACE II genotype (OR = 1.84, 95% CI = 1.30, 2.61; < 0.01) and the I allele (OR = 1.51, 95% CI = 1.22, 1.86; < 0.01) was significantly higher in psoriasis patients compared to the control group. Conversely, the frequency of the ACE DD genotype (OR = 0.62, 95% CI = 0.44, 0.87; < 0.01) and the D allele (OR = 0.66, 95% CI = 0.54, 0.82; < 0.01) was significantly lower in psoriasis patients compared to the control group. No statistically significant differences were observed when stratified by blood pressure and blood glucose abnormalities ( > 0.05). The ACE II genotype and I allele are risk factors for psoriasis vulgaris in the Northern Chinese Han population.